2013
DOI: 10.1158/1078-0432.ccr-12-3289
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK3B Bypass Drug Resistance of p53-Null Colon Carcinomas by Enabling Necroptosis in Response to Chemotherapy

Abstract: Purpose: Evasion from chemotherapy-induced apoptosis due to p53 loss strongly contributes to drug resistance. Identification of specific targets for the treatment of drug-resistant p53-null tumors would therefore increase the effectiveness of cancer therapy.Experimental Design: By using a kinase-directed short hairpin RNA library and HCT116p53KO drugresistant colon carcinoma cells, glycogen synthase kinase 3 beta (GSK3B) was identified as a target whose silencing bypasses drug resistance due to loss of p53. p5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 48 publications
2
64
0
2
Order By: Relevance
“…Unlike most kinases, GSK3β is constitutively active by dephosphorylation and high levels of GSK3β activity promote cell death 39 . Our findings indicate a potential link between AURKA, GSK3β, and Wnt/β-catenin pathways in the regulation of necroptosis 28, 41, 42 .…”
Section: Discussionmentioning
confidence: 66%
“…Unlike most kinases, GSK3β is constitutively active by dephosphorylation and high levels of GSK3β activity promote cell death 39 . Our findings indicate a potential link between AURKA, GSK3β, and Wnt/β-catenin pathways in the regulation of necroptosis 28, 41, 42 .…”
Section: Discussionmentioning
confidence: 66%
“…1D, miR-520g expression was high in FET cells with mutated p53 (35) and low in HCT116 and RKO cells with WT p53 (35,36). p53 has been implicated to contribute to 5-FU-and other chemotherapeutic drug-induced apoptosis, which involves the DNA damage response (18,37). We therefore hypothesized that p53 suppresses miR-520g expression in colon cancer cells.…”
Section: Mir-520g Increases Drug Resistance By Reducing the Expressiomentioning
confidence: 95%
“…Although there is a lack of literature about it, in a recent work from Grassilli and colleagues, it was demonstrated that glycogen synthase 3 b (GSK3B), a serine-threonine kinase belonging to the glycogen synthase kinase subfamily that is involved in energy metabolism, neuronal cell development, and body pattern formation, was activated in almost 50% of colon carcinomas and in two thirds of drug-resistant ones. Genetic silencing of GSK3B in p53-null cells treated with oxaliplatin induced cell death by caspase-independent necroptotic death (78). It is noteworthy that oxaliplatin effectiveness has been associated with the production of ROS, which in turn is a contributor to the execution of necrosis (76).…”
Section: Regulated Necrosismentioning
confidence: 99%